Development of Two Language Picture Cards for Javanese Introduction to Early Childhood - Agatha Puspita Febiyanti Agatha; Putri Nur Rahmawati; Retno Dewi Yatmi Retno; Arneta Prabani Arneta; Joko Pamungkas Joko (ABNA : Journal of Islamic Early Childhood Education, 2022)
Abstract Early childhood education is an important period and needs attention. At this age children experience very rapid development. In the implementation of education in Kindergarten schools, teachers serve children's education through teaching that is adapted to the curriculum. However, nowadays it is still rare for kindergarten institutions in the Special Region of Yogyakarta to apply local potential in their area, one of which is local wisdom to introduce Javanese language to children in kindergarten. The purpose of this study was to test the feasibility of a learning media developed by researchers to support learning with local wisdom introduction to the Javanese language, namely bilingual picture cards. The method used in this research is the Research and Development method using the ADDIE model. Bilingual picture cards as learning media that have been made are tested and applied to teachers who teach children aged 4-6 years in Kindergarten in the Gunung Kidul area using a coaching clinic strategy. Keyword : early childhood, local wisdom, Javanese language Abstrak Pendidikan anak usia dini merupakan masa penting dan perlu diperhatikan. Pada usia ini anak mengalami perkembangan yang sangat pesat. Dalam pelaksanaan pendidikan di sekolah Taman Kanak-kanak, para guru melayani pendidikan anak melalui pengajaran yang disesuaikan dengan kurikulum. Namun, saat ini masih jarang lembaga TK di Daerah Istimewa Yogyakarta yang menerapkan potensi lokal di daerahnya, salah satunya adalah kearfian lokal untuk mengenalkan Bahasa Jawa pada anak di TK. Tujuan penelitian ini adalah untuk menguji kelayakan suatu media pembelajaran yang dikembangakan oleh peniliti guna mendukung pembelajaran dengan kearifan lokal pengenalan Bahasa Jawa, yaitu kartu bergambar dua bahasa. Metode yang dilakukan dalam penelitian ini yaitu metode Research and Development menggunakan model ADDIE. Kartu bergambar dua bahasa sebagai media pembelajaran yang telah dibuat diujikan dan diterapkan pada guru yang mengajar anak usia 4-6 tahun di TK wilayah Gunung Kidul dengan menggunakan strategi coaching clinic. Kunci Kunci : anak usia dini, kearifan lokal, Bahasa Jawa